Evaluation of Housing Development Growth in Asahan Regency: English - Suharizki, Eko; Nasution, Zulkifli; Purwoko, Agus; Lubis, Arga Abdi Rafiud Darajat (CV. ARGA FARMA, 2024)
This study aims to evaluate the factors influencing housing development growth in Asahan Regency and to assess the socio-economic impacts on the local community. The research focuses on the transition of land use from agricultural to non-agricultural purposes, examining the driving determinants and the consequent socio-economic effects. Utilizing both primary data from interviews and questionnaires and secondary data from official statistics and literature, the study employs multiple regression analysis to identify key factors such as location, price, facilities, and accessibility. The findings indicate that while these factors positively influence housing development growth, their significance varies. The study also highlights the socio-economic impacts, including job displacement for farmers, reduced social interaction, social stratification, and new employment opportunities. Recommendations are made for better land management and the development of new agricultural areas to ensure sustainable growth.